Efficacy of teachers’ semi-focused written corrective feedback on learners’ linguistic accuracy and writing fluency - Ekanayaka, Waruni Iresha (Curtin University, 2022)
This thesis presents a quasi-experimental study carried out to examine the effect of teachers’ semi-focused written corrective feedback (WCF) on a group of intermediate-level learners’ linguistic accuracy and writing fluency over a period of 10 weeks. It also explores the learners’ perceptions towards feedback. This study showed that multiple provisions of WCF led to accuracy improvements in finite verb constructions.